An Equilibrium Theory of Rationing. - Gilbert, R; Klemperer, P (2000)
Committing to prices that result in rationing may be more profitable than setting market-clearing prices if customers must make sunk investments to enter the market. Rationing is ex post inefficient, but it gives more surplus to lower-value customers who are the marginal consumers the monopolists want to tempt to make investments. Similarly, a monopsonist may procure some requirements from high-cost "second sources" rather than purchase only from the lowest-cost suppliers. The model contributes to the theory of auctions with endogenous entry, and it may also help explain "efficiency wages," "second prizes," and "fair" behavior.